Metacognitive Online Discussion for Online Teaching: A Conceptual and Impact on Students Engagement and Mastery During Coronavirus Outbreaks - Mohamad Ariffin Abu Bakar , Norulhuda Ismail (International Journal of Advanced Science and Technology, 2020)
The online teaching is proposed as a platform to continue learning sessions during outbreaks. It is essential to introduce online teaching activity model that strengthen student metacognitive regulation skills in order to maintain active learning and to ensure students mastery of the mathematics concepts at the optimum level. This concept paper exposes the development and impact of a metacognitive regulation learning strategy model in the process of creating an online teaching activity. This discussion interacts with both the needs and elements of the online learning concept. The implications provide guidance and suggestions for developing effective mathematics teaching and learning sessions through online platforms, especially for those in need of a social distancing crisis